Impaired K48-polyubiquitination downmodulates mouse norovirus propagation - Emmrich Wakeford; Elisabeth Werkmeister; Delphine Cayet; Sabine Poiret; Catherine Daniel; Jason Mackenzie; Jean-Claude Sirard; Frank Lafont; Ghaffar Muharram (Frontiers in Cellular and Infection Microbiology)
IntroductionNoroviruses are small non-enveloped, single stranded positive-sense RNA viruses that belong to the family Caliciviridae. They are highly contagious and resistant to multiple detergents and are the infectious agents in the majority of viral gastroenteritis in adults. Due to a lack of approved preventive or curative therapy options, intensive research effort is ongoing to better understand the pathogenesis mechanisms of noroviruses.MethodsIn this study, using the persistent murine norovirus S99 strain (MNoV_S99), we have investigated the role in the regulation of anti-noroviral responses of ubiquitination, a post-translational modification that covalently adds one or multiple ubiquitin molecules onto lysine residues of target proteins. To that end, we have first generated RAW264.7 cells overexpressing YFP-Ubiquitin_WT, _K29R, _K48R or_K63R constructs. All non-WT constructs encode a ubiquitin fusion protein with one lysine mutated into an arginine residue, thus preventing the formation of the K29-, K48- or K63-dependent polyubiquitin chains respectively.ResultsUpon infection of these cells with MNoV_S99, we unexpectedly observed that only cells expressing the YFP-Ubiquitin_K48R protein showed a significantly impaired expression of several viral markers: NS5, NS7, VP1 and the replication intermediate dsRNA. Consequently, the number of viral genome copies or viral titers were also significantly decreased in the YFP-Ubiquitin_K48R cells compared to the YFP-Ubiquitin_WT cells. This negative regulation cannot be explained by perturbed viral entry, but rather a constitutive hypersecretion of the pro-inflammatory cytokine TNF and downstream upregulation of IκBα phosphorylation and the subsequent NF-κB nuclear translocation.ConclusionOverall, these consequences combined impose a non-permissive environment for MNoV_S99 replication and propagation.